DEVELOPMENT OF NATIONAL CREATIVE INDUSTRIES: COMPARISON OF FOREIGN AND DOMESTIC EXPERIENCE - Saktaganov Balabek; Doszhan Raikhan (Reviews of Modern Science, 2024)
The article considers the creative economy as a rapidly developing sector of the international economy. Special attention is paid to the priority position of creative industries in public policy of different countries. The study includes the analysis of international classifiers of activities in this sphere, as well as a comparative analysis of policies for the development of creative industries in Great Britain, Germany and Kazakhstan. The conclusions point to the initial stage of development of the domestic model of creative industries due to insufficient legal regulation and systemic support.